Parâmetros genéticos para peso corporal e características reprodutivas em codornas de corte - Vogado, Gleissa Mayone Silva (2022)
The objective of this work was to evaluate methods of phenotypic selection in beef quails through weight collection (in grams) at 28 days of life (P28), notes of age at first egg (in days) (IPO), verification of the age of sexual maturity in males (in days) (IMSM), measurements of paracloacal gland area in males (in mm2) (AGPM), determinations for ovarian weight (in grams) (POVR), and measurements of testis weight (in grams) (PTEST). In this study, a total of 287 female and 159 male beef quails from two subsequent generations were used. Heritabilities (h2), genetic (rG) and residual (rR) correlations between traits were estimated using the GIBBS1F90 program. The estimates of h2 (credibility interval: CI) were 0.47 (0.40; 0.52), 0.14 (0.06; 0.29), 0.16 (0.08; 0.25) , 0.28 (0.15; 0.41), 0.25 (0.14; 0.40) and 0.36 (0.21; 0.52) for P28, IMSM, AGPM, IPO, POVR and PTEST, respectively. In the estimation of rG (CI) for P28 they were -0.04 (-0.38; 0.28), 0.23 (-0.07; 0.55), 0.05 (-0.18; 0. 31), 0.40 (0.11; 0.70) and 0.70 (0.45; 0.89) among IMSM, AGPM, IPO, POVR and PTEST respectively; for IMSM were -0.52 (-0.86; -0.19), 0.38 (-0.01; 0.79), 0.5 (0.08; 0.92) and 0.07 ( -0.37, 0.51) between AGPM, IPO, POVR and PTEST, respectively; for AGPM it was -0.46 (-0.82; -0.05), -0.35 (-0.76; 0.17) and 0.29 (-0.18; 0.66) between IPO, POVR and PTEST, respectively; for IPO they were 0.26 (-0.10; 0.64) and 0.06 (-0.31; 0.59) between POVR and PTEST, respectively; and finally for POVR it was -0.14 (-0.45; 0.20). For the estimation of rR (CI) for P28 they were 0.11 (-0.09; 0.15), 0.19 (0.06; 0.31), 0.06 (-0.05; 0.20 ), 0.14 (-0.09; 0.38) and 0.03 (-0.24; 0.28) among IMSM, AGPM, IPO, POVR and PTEST respectively; for IMSM they were -0.14 (-0.24; -0.05) and -0.11 (-0.30; 0.11) between AGPM and PTEST, respectively; for AGPM it was 0.15 (-0.07; 0.33) between PTEST; and finally IPO was -0.21 (-0.42; -0.01) among POVR. The results obtained for h2 showed moderate to low data for the multitrait, indicating a greater need for control of phenotypic selection in animal reproduction, since the selection practiced in the herd is based on individual information. The highest significant correlation was between P28 and PTESTE, denoting that this correspondence is considered an indication of fertility, since the reduction in body weight of beef quails is normally in consort with the limitation of spermatogenesis production, resulting in the reproductive ability of these animals. . Thus, the phenotypic selection treated intensively for weight gain of these birds, causing the depreciation of the capacity of the reproductive age of the meat quails. However, measures of reproductive efficiency are often expensive or complex to collect, requiring simple traits for sire selection.